Pengaruh Fundamental Tournament Models Terhadap Teknik Dasar Dalam Pembelajaran Sepak Bola di SMA Negeri 1 Tambun Utara - Mulyana, Arif; Fahrudin, Fahrudin; Achmad, Irfan Zinat (Peneliti.net, 2024)
This study is motivated by the difficulty in the ability of basic soccer techniques and the lack of motivation of students' enthusiasm for learning because of boring learning. This study aims to determine how much the influence of fundamental tournament models in improving the ability of basic soccer techniques of class XI students of SMAN 1 Tambun Utara in carrying out PE learning. This research is a quantitative study, using the quasi-experimental method or called a pseudo-experiment with a research instrument in the form of a test. The population of this study was 144 students. While the sample taken in this study using cluster random sampling, the sample size taken in this study amounted to 36 students in one class. Data collection using tests, with the instrument used in the form of a sports skills test sourced from Dr. M.E. Winarno, M.Pd (2012). Because the research data was not normally distributed, this data analysis used the Wilcoxon test with the help of SPSS 25. The results of this study obtained the following conclusions: It is known, the results of the data analysis test using the wilcoxon test get positive ranks with mean rank = 18.50 and sum of ranks = 666.00 so there is a positive increase from pretest to posttest. Which means that there is a positive influence after applying the fundamental tournament learning model on basic techniques in learning soccer games at SMAN 1 Tambun Utara.